Analysis of the Relationship between Clean Living Behavior and Environmental Sanitation in Thyfoid Patients - Sianturi, Reksaudi; Ginting, Chrismis Novalinda; Nasution, Sri Wahyuni (Newinera Publisher, 2024)
Typhoid fever is often experienced by children and teenagers. This happens because they do not realize the importance of food and environmental cleanliness. Typhoid fever is related to the patient's environment and behavior. Prevention of typhoid disease must be linked to clean and healthy living habits such as maintaining a hygienic diet and a clean and comfortable environment, especially for children who do not pay attention to cleanliness and health. The aim of this research is to analyze the relationship between clean living behavior and environmental sanitation in Thyphoid patients at DR Pirngadi Regional Hospital, Medan. This type of research is an analytical survey with a cross-sectional design. The population in this study were typhoid patients at DR Pirngadi Medan Hospital in 2023 for the period January 2023 – September 2023, totaling 585 patients. Determining the sample used interpretive estimation with Structural Equation Modeling (SEM) where the number of samples in this study was 150 samples. Data analysis in this study used univariate, bivariate and multivariate analysis. The results of the research show that there is a relationship between clean living behavior in Thyphoid patients at DR Pirngadi Hospital, Medan, p - value < 0.05, there is a relationship between environmental sanitation in Thyphoid patients at DR Pirngadi Hospital, Medan, p - value < 0.05, simultaneously There is a relationship between clean living behavior and environmental sanitation in Thyphoid patients at DR Pirngadi Hospital, Medan, p - value < 0.05.